Stoichiometry and kinetics of the anaerobic ammonium oxidation (Anammox) with trace hydrazine addition. (December 2015) - Yao, Zongbao; Lu, Peili; Zhang, Daijun; Wan, Xinyu; Li, Yulian; Peng, Shuchan
Highlights: Stoichiometric coefficients of Anammox with trace hydrazine addition were obtained. Kinetics of Anammox process with trace hydrazine addition was investigated. Kinetic parameters of Anammox with trace hydrazine addition were identified. The biochemical mechanism of enhancement via N2 H4 addition was discussed. Abstract: Purpose of this study is to investigate the stoichiometry and kinetics of anaerobic ammonium oxidation (Anammox) with trace hydrazine addition. The stoichiometry was established based on the electron balance of Anammox process with trace N2 H4 addition. The stoichiometric coefficients were determined by the proton consumption and the changes in substrates and products. It was found that trace N2 H4 addition can increase the yield of Anammox bacteria (AnAOB) and reduce NO3 − yield, which enhances the Anammox. Subsequently, kinetic model of Anammox with trace N2 H4 addition was developed, and the parameters of the anaerobic degradation model of N2 H4 were obtained for the first time. The maximum specific substrate utilization rate, half-saturation constant and inhibition constant of N2 H4 were 25.09 mg N/g VSS/d, 10.42 mg N/L and 1393.88 mg N/L, respectively. These kinetic parameters might provide important information for the engineering applications of Anammox with trace N2 H4 addition.